Utilizing AR-Book to Enhance Reading Interest at SCU Library - Adirati, Melania (Soegijapranata Catholic University, 2025)
This study examines how augmented reality (AR) technology impacts students' interest in reading in SCU Libraries, specifically AR-Books. The primary objective was to determine how AR-Books can increase student engagement and motivation. We used a descriptive qualitative research method and conducted open-ended interviews with eight students with AR-Books experience. The findings positively impacted reading interest; participants noted that AR-Book summaries provided a better experience due to their time efficiency and interactive features. Interestingly, all students desired to continue using AR-Books, underscoring their effectiveness in creating a more engaging reading experience. Overall, AR-Books are a valuable resource for increasing students' reading interest, aligning with the younger generation's preference for quick and convenient solutions.